A Case of Brief Psychotic Disorder and its Homoeopathic Management (Advancements in Homeopathic Research, 2017)
Brief Psychotic Disorder may appear in adolescence or early adulthood, with the average age at onset being in the late 20s or early 30s.Individuals with Brief Psychotic Disorder typically experience emotional turmoil or overwhelming confusion. They may have rapid shifts from one intense affect to another. Although brief, the level of impairment may be severe, and supervision may be required to ensure that nutritional and hygienic needs are met and that the individual is protected from the consequences of poor judgment, cognitive impairment, or acting on the basis of delusions. There appears to be an increased risk of mortality (with a particularly high risk for suicide), especially among younger individuals1. A case of brief Psychotic episode admitted at NHRIMH (former CRIH), Kottayam and treated with Phosphorus is reported here.
Keywords: Brief psychotic disorders; Homoeopathy; Case taking; Individualistic treatment; Phosphorous